Metastable, Spintronics Materials and Mechanics of Deformable Bodies Recent Progress - Sivasankaran, Subbarayan; Kumar Nayak, Pramoda; Günay, Ezgi (IntechOpen, 2020)
This book describes the recent evolution of solid-state physics, which is primarily dedicated to examining the behavior of solids at the atomic scale. It also presents various state-of-the-art reviews and original contributions related to solid-state sciences. The book consists of four sections, namely, solid-state behavior, metastable materials, spintronics materials, and mechanics of deformable bodies. The authors' contributions relating to solid-state behavior deal with the performance of solid matters pertaining to quantum mechanics, physical metallurgy, and crystallography. The authors' contributions relating to metastable materials demonstrate the behavior of amorphous/bulk metallic glasses and some nonequilibrium materials. The authors' contributions relating to spintronic materials explain the principles and equations underlying the physics, transport, and dynamics of spin in solid-state systems. The authors' contributions relating to the mechanics of deformable bodies deal with applications of numeric and analytic solutions/models for solid-state structures under deformation. Key Features:Issues in solid-state physics, Lagrangian quantum mechanics,Quantum and thermal behavior of HCP crystals,Thermoelectric properties of semiconductors,Bulk metallic glasses and metastable atomic density determination,Applications of spintronics and Heusler alloys, 2D elastostatic, mathematical modeling and dynamic stiffness methods on deformable bodies.